Pengaruh Current Ratio Dan Total Asset Turnover Terhadap Pertumbuhan Laba Pada Pt Arwana Citramulia Tbk Periode 2015-2024 - Dera Yowananda Setyawan; Hasanudin Hasanudin (Journal of Innovative and Creativity, 2026)
This study aims to determine the partial effect of the current ratio and total asset turnover on profit growth, as well as to determine the simultaneous effect of the current ratio and total asset turnover on profit growth at PT Arwana Citramulia Tbk for the 2015–2024 period. The samples used in this study were the financial position report (balance sheet) and income statement. The research method used in this study is quantitative with a descriptive approach. The data analysis techniques employed include descriptive tests, classical assumption tests, multiple linear regression analysis, the coefficient of determination, and hypothesis testing, with data processing carried out using IBM SPSS 26. The results of the study indicate that partially, the current ratio has no significant effect on profit growth, as shown by the t-value of 1.069 < t-table 2.364, with a significance value of 0.321 > 0.05. Conversely, total asset turnover has a significant effect on profit growth, with a t-value of 3.382 > t-table 2.364 and a significance value of 0.012 < 0.05. Simultaneously, both variables significantly influence profit growth, as evidenced by the F-value of 7.035 > F-table 4.737 and a significance value of 0.021 < 0.05. Furthermore, the coefficient of determination obtained is 0.573, indicating that the current ratio and total asset turnover contribute only 57.3% to profit growth, while the remaining percentage is influenced by other variables outside this study.